Suche nach einer stabilen, verlässlichen und solidarischen Finanzierung der gesetzlichen Krankenversicherung - Wolfgang Greiner; Julian Witte; Daniel Gensorowsky (Wirtschaftsdienst, 2024)
– The German Federal Government has initiated key projects and reforms for the future development of healthcare in Germany. These include political initiatives for deregulation, digitisation, and large-scale structural projects. However, rather than directly contributing to the relief of the financial situation in the statutory health insurance (SHI), these initiatives inherently require investment and increased expenditure. It is therefore imperative that stabilisation of the SHI finances accompany structural healthcare reforms. Therefore, sustainable development of the SHI must include transparency about reform options, reliable data on their expected effects, and the will to critically evaluate them.
Keywords: H51; I11; I18; 330; Gesetzliche Krankenversicherung; Gesundheitsreform; Deutschland; Gesetzliche Krankenversicherung; Gesundheitsreform; Deutschland